Pengaruh Sertifikasi Terhadap Kinerja Guru di SMA N 1 Gianyar - Dewanto, Dharmawan Haryo; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2016)
ABSTRACT The Influence of Teacher’s Certification Program towards Teacher’s Performance at SMA N 1 Gianyar Education is an important aspect for a nation to developing their Human Resources and National Character Building. The dignity of a nation is depends on their education quality. The role of a teacher is very important, therefore The Government of Indonesia implementing a certification program to maintain the quality and the professionalism of teachers.In this research, SMAN 1 Gianyar became a research object where SMAN 1 Gianyar is considered as one of the best school in Gianyar Regency, which is hoped could become a prototype for another school in Gianyar Regency.The purpose of this research is to find an emphirical evidence about the influence of Teacher’s Certification toward teacher’s performance. This research is using Taro Yamane technique. The Collection of the research data is by giving an open questionnaire to 42 State Teacher at SMAN 1 Gianyar. The indicator in this research is tested with validity and reliability test. The test on the hypothesis is using double linear regression analysis. The result including Pedagogical Competence, Professionalism Competence, Social Competence and Behavioral Competence are related with Learning Activities Planning, Implementation and Appraisal with the correlation coefficient number marked with correlation coefficient(RSquare) with R symbol is 0,483. The number of (RSquare) is a sign that showing the Influence of Teacher’s Certification toward Teacher’s Performance at SMAN 1 Gianyar. Keywords : Certification, Teacher’s Performance